2011
DOI: 10.1002/mc.20842
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of matrix metallopeptidase 3 and risk of gliomas in a Chinese Han population

Abstract: Matrix metallopeptidases (MMPs) play an important role in central nervous system tumor growth, invasion and spreading. The currently available data provide clear evidence for the involvement of MMP3 in the pathophysiology of glioma. The study aims to explore the association of single nucleotide polymorphisms (SNPs) across the MMP3 gene with glioma risk. Three haplotype tagging and additional two promoter SNPs were genotyped among 766 glioma patients and 824 cancer-free controls from East China. None of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The current study also revealed that the protein levels of MMP-2, MMP-9, and Vimentin were increased, while the E-cadherin protein level was decreased as a result of BMP2 over-expression or activation of the MAPK/p38 signaling pathway. The MMP family represents the dominating factors in promoting central nervous system tumor growth, including invasion and spreading, and thereby is of valuable therapeutic importance [31]. In addition, it has been reported that MMP-2 activation induced by the ERK/MAPK signaling pathway contributes to the enhancement of cell proliferation and invasion in endometrial cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…The current study also revealed that the protein levels of MMP-2, MMP-9, and Vimentin were increased, while the E-cadherin protein level was decreased as a result of BMP2 over-expression or activation of the MAPK/p38 signaling pathway. The MMP family represents the dominating factors in promoting central nervous system tumor growth, including invasion and spreading, and thereby is of valuable therapeutic importance [31]. In addition, it has been reported that MMP-2 activation induced by the ERK/MAPK signaling pathway contributes to the enhancement of cell proliferation and invasion in endometrial cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of RNA-seq, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that gene sets that were significantly differentially regulated in GMPPB knockdown cells were mainly involved in cell adhesion, axon guidance, and Hippo signaling pathways (Figure 5B). Intriguingly, we also detected MMPs (Figure 5A,D), a gene that has been previously reported to play an important role in the malignancy of glioma cells [31,[37][38][39], as one of the downstream target genes of GMPPB. Indeed, the expression of MMP3 was decreased by down-regulating GMPBB, while in GBM cells, over-expressing GMPPB increased the expression levels of MMP3 in GBM cells (Figure 5E).…”
Section: Silencing Gmppb Inhibits the Proliferation And Invasion Of G...supporting
confidence: 63%
“…For instance, elevated expression of MMP3 has been detected in human astrocytoma, especially in invasive glioma cells. Increased cytoplasmic MMP3 expression stimulates glioma cell invasiveness and migration [29][30][31] , making MMP3 a promising therapeutic target. The current study showed that MMP3 could be induced by GBP5 at both mRNA and protein levels in GBM cells and was essential for GBP5-driven impacts.…”
Section: Discussionmentioning
confidence: 99%